KAJIAN PARTISIPASI MASYARAKAT PESISIR DALAM PROGRAM SANITASI PERKOTAAN BERBASIS MASYARAKAT (SPBM) DI DESA GEGUNUNG WETAN KECAMATAN REMBANG KABUPATEN REMBANG - Dwimawanti, Ida Hayu; Zakiyya, Ifwanda Mar’atuz (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The Urban Sanitation and Rural Infrastructure in the form Facility Development Communal WWTP (waste water treatment plant) and latrines. Defecation in the beach is still done by societies of Gegunung Wetan Village. The purpose of this study to reviewing stages of participation, factors that inhibit societies’ participation, and formulating the efforts to solve those factors that inhibit participation in The Urban Sanitation and Rural Infrastructure in the Gegunung Wetan village. The method used is descriptive qualitative. The planning stage is dominated by public figures, while societies as the listener. The implementation stage of development only involves the society around the construction area. Societies use The Urban Sanitation and Rural Infrastructure facilities rarely and they did not conduct monitoring and evaluating The Urban Sanitation and Rural Infrastructure facilities. Factors inhibiting communities participation in the The Urban Sanitation and Rural Infrastructure is age, work, gender, volition, chance, mindset, distance, regulation, habit, and duration of stay. To foster their participation is through community service, making the schedule to maintain it, and encourage children playgroup to optimize program results. Overcoming the obstacle by impose sanctions that arranged in the Regulation village about prohibition defecation on the beach, held competition household level about healthy hygienic behavior, publish photos of people who were defecation on the beach, socialize The Urban Sanitation And Rural Infrastructure, urges healthy hygienic behavior, applying of Toilet Training.